2023
DOI: 10.3221/igf-esis.65.12
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Micro-structure, Hardness and Optimization of Wear Characteristics of Al6061/TiB2/CeO2 Hotrolled MMCs using Taguchi Method

Abstract: Aluminium composites are extensively used in several industrial applications. The production of Metal Matrix Composite (MMCs) with varying wt. % of reinforcement/s leads to enhancement of wear and mechanical behavior. In the present work, the varying wt. % of TiB2 and constant wt. % of CeO2 particulates were reinforced in Al6061 alloy to manufacture hybrid Al MMCs by Vortex (Stircasting) technique. Developed hybrid MMCs were hotrolled at 515°C of temperature. Hardness of hybrid MMCs was evaluated by using hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…10 shows a major effect graph that centers on Ra values with the goal of identifying the ideal machining parameters that lead to the best possible surface quality. The graph clearly shows that the most advantageous points in this study, which correlate with improved surface texture of composites, are: level-1 of nano-B 4 C, level-1 of nano-Al 2 O 3 , and level-3 of ageing temperature [12]. It was shown that as the ageing temperature increased, Ra decreased.…”
Section: Cutting Force and Ramentioning
confidence: 59%
See 1 more Smart Citation
“…10 shows a major effect graph that centers on Ra values with the goal of identifying the ideal machining parameters that lead to the best possible surface quality. The graph clearly shows that the most advantageous points in this study, which correlate with improved surface texture of composites, are: level-1 of nano-B 4 C, level-1 of nano-Al 2 O 3 , and level-3 of ageing temperature [12]. It was shown that as the ageing temperature increased, Ra decreased.…”
Section: Cutting Force and Ramentioning
confidence: 59%
“…In the current study, the primary reason for the MMCs' reduced ductility was interface debonding. Furthermore, the primary factor causing the quick failure of MMCs is the presence of nano-sized B 4 C/Al 2 O 3 particle clusters, which likewise have no effect on the tensile strength of MMCs at increasing weight percentages of nano reinforcements[11,12].…”
mentioning
confidence: 99%